Nomogram prediction of overall survival based on log odds of positive lymph nodes for patients with penile squamous cell carcinoma. (10th June 2020) - Zheng, Wenwen; Li, Kangqi; Zhu, Weiwei; Ding, Yuexia; Wu, Qingna; Tang, Qiling; Lu, Congxiao; Zhao, Quan; Yu, Shengqiang; Guo, Chenyu
Abstract: Purpose: This study aimed to establish a nomogram to predict the long‐term overall survival (OS) for patients with penile squamous cell carcinoma (PSCC). Method: The PSCC patients receiving regional lymph node dissection (RLND) were enrolled from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2015. The dataset of all eligible patients were used to develop the predictive model. The significant independent predictors were identified through Cox regression modeling based on the Bayesian information criterion and then incorporated into a nomogram to predicted 1‐, 3‐, and 5‐year OS. Internal validation was performed using the bootstrap resampling method. The model performance was evaluated using Harrell's concordance index (C‐index), calibration plots, integrated discrimination improvement (IDI), net reclassification improvement (NRI), and decision curve analysis (DCA). Results: Totally, 384 eligible PSCC patients were enrolled from the SEER database. A nomogram for OS prediction was developed, in which three clinical variables significantly associated with OS were integrated, including age, N classification, and log odds of positive lymph nodes (LODDS). The C‐index of the nomogram (0.746, 95% CI: 0.702‐0.790) was significantly higher than that of the American Joint Committee on Cancer (AJCC) staging system (0.692, 95% CI: 0.646‐0.738, P = .020). The bootstrap optimism‐corrected C‐index for the nomogram was 0.739 (95% CI: 0.690‐0.784). The bias‐corrected calibration plots showed the predicted risks were in good accordance with the actual risks. The results of NRI, IDI, and DCA exhibited superior predictive capability and higher clinical use of the nomogram compared with the AJCC staging system. Conclusion: We successfully constructed a simple and reliable nomogram for OS prediction among PSCC patients receiving RLND, which would be beneficial to clinical trial design, patient counseling, and therapeutic modality selection. Abstract : In this study, we successfully constructed a simple and reliable nomogram for survival prediction among patients with penile squamous cell carcinoma. Three clinical variables were integrated into the model, including age, N classification, and log odds of positive lymph nodes. Compared to the AJCC staging system, the established nomogram exhibited superior predictive ability and clinical use.